Evaluation of in vitro and in vivo anti-arthritic potential of Berberis calliobotrys (Bangladesh Journal of Pharmacology, 2015)
The present study was commenced to evaluate the anti-arthritic effect of 70% methanol extract and n-butanol and aqueous fractions of Berberis calliobotrys using both in vitro and in vivo arthritis models. Extract and fractions were investigated in vitro for inhibition of protein (bovine serum and egg albumin) denaturation and human red blood cell membrane stabilization. In vivo anti-arthritic activity of extract and fractions at 50, 100 and 200 mg/kg was assessed using turpentine oil and formaldehyde-induced arthritis, while, 200 mg/kg dose was evaluated against complete Freunds adjuvant-induced arthritis. B. calliobotrys produced significant (p